2021
DOI: 10.3390/ijerph182111234
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Contextual Factors Associated with Malaria among Children 6–59 Months in Nigeria: A Multilevel Mixed Effect Logistic Model Approach

Abstract: Background/Purpose: Over the last two decades, malaria has remained a major public health concern worldwide, especially in developing countries leading to high morbidity and mortality among children. Nigeria is the world most burdened malaria endemic nation, contributing more than a quarter of global malaria cases. This study determined the prevalence of malaria among children at 6–59 months in Nigeria, and the effects of individual and contextual factors. Methods: This study utilized data from 2018 Nigeria De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 35 publications
5
30
0
Order By: Relevance
“…For instance, a negative association was found between malaria infection and mothers’ education as malaria prevalence was higher among children whose mothers did not attend school (61.5%) compared to those whose mothers had secondary or higher education (11.3%). This finding agrees with previous studies that reported a similar association between maternal education and malaria prevalence among children [ 16 , 30 , 31 ]. Low educational status among mothers may facilitate poor knowledge of malaria prevention, risk factors, and symptoms leading to higher malaria prevalence among their children [ 9 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For instance, a negative association was found between malaria infection and mothers’ education as malaria prevalence was higher among children whose mothers did not attend school (61.5%) compared to those whose mothers had secondary or higher education (11.3%). This finding agrees with previous studies that reported a similar association between maternal education and malaria prevalence among children [ 16 , 30 , 31 ]. Low educational status among mothers may facilitate poor knowledge of malaria prevention, risk factors, and symptoms leading to higher malaria prevalence among their children [ 9 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…The logistic regression model in this study revealed that six out of the nine included independent variables (under-five child’s age, maternal education, female of household head, household wealth index, place of residence, and African region where mother–child pair lives) had statistically significant associations with malaria prevalence among under-five children assessed. This finding is similar to those documented by previous studies conducted in the SSA region [ 1 , 11 , 16 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ICC com is used to evaluate whether the community factors are more relevant in explaining the variation in the outcome variable and establish the need for the multilevel analysis [ 38 , 40 ]. The higher the ICC, the larger the contribution of the community factors in explaining the variation, and an ICC of less than 5% at the null model suggests that hierarchical modelling may not be necessary [ 42 ]. The PCV, which indicates the additional effects of the included variables (individual- and community-level factors), is calculated as [PCV = ], where V e is the variance in the null model and V m is the variance in the successive models.…”
Section: Discussionmentioning
confidence: 99%
“…A likelihood ratio test was performed after each multilevel logistic regression to determine whether two-level model was more appropriate than individual-level model [ 57 , 58 ]. In addition, Akaike’s information criterion (AIC) and Bayesian information criterion (BIC) were utilized to check fitness of different models [ 59 ].…”
Section: Methodsmentioning
confidence: 99%